Association of qnr Genes and OqxAB Efflux Pump in Fluoroquinolone-Resistant Klebsiella pneumoniae Strains - Fereshteh Amereh; Mohammad Reza Arabestani; Seyed Mostafa Hosseini; Leili Shokoohizadeh (International Journal of Microbiology)
Background. The aim of this study was to investigate the frequency and relationship between plasmid-mediated quinolone resistance genes and OqxAB pump genes, as well as the genetic linkage in K. pneumoniae strains isolated from Hamadan hospitals in the west of Iran. Materials and Methods. In this study, 100 K. pneumoniae clinical strains were isolated from clinical samples of inpatients at Hamadan Hospital in 2021. The antimicrobial susceptibility testing was performed using the disk diffusion method. The frequencies of genes encoding OqxAB efflux pumps and qnr were investigated by PCR. Molecular typing of qnr-positive K. pneumoniae isolates was assessed by ERIC-PCR. Results. Antibiotic susceptibility testing showed high resistance (>80%) to fluoroquinolones. The gene encoding the OqxAB efflux pump was detected in more than 90% of K. pneumomiae strains. All K. pneumoniae isolates were negative for qnrA, and 20% and 9% of the isolates were positive for qnrB and qnrS, respectively. The genes encoding oqxA and oqxB were detected in 96% of qnr-positive strains. A qnrB + /qnrS + profile was observed in 16% of qnr-positive K. pneumoniae strains. Ciprofloxacin MIC ≥ 256 μg/ml was detected in 20% of qnr-positive strains. Genetic association analysis by ERIC-PCR revealed genetic diversity among 25 different qnr-positive strains of K. pneumonia. Conclusion. However, no significant correlation was found between the qnr and the OqxAB efflux pump genes in this study. The high rate of fluoroquinolone resistance and determinants of antibiotic resistance among diverse K. pneumoniae strains increase the risk of fluoroquinolone-resistance transmission by K. pneumoniae strains in hospitals.